Analisis Efisiensi Usaha Kerajinan Gerabah Di Jombang - Jatmiko, Anang Rohmad; Fathur Rohman, Mohamad (eBA Journal: Journal Economics, Bussines and Accounting, 2016)
This research aims for recognise the size of gain and efficient of processing ground into gerabah in Tondowulan. Basic method that used is descriptive method. Defining research place was did by deliberate (purposive) i.e. in Tondowulan according the reason of the worker in there make a Gerabah by did making process until done. Type of data that use is primer’s data with use technique; observe, interview, and documentation. Analysis method that used is trade analysis for recognise the gain, efficient. The result show if the gain that received from Gerabah industry in one time running process is Rp. 521.033,8. In the other hand, the efficiency of Gerabah industry in Tondowulan is  1,76 %. So the industry of Gerabah could say it is efficient because of, for example if that industry going out Rp 100.000 as asset, the will get Rp176.000 as their gain.